Curtailing virus-induced inflammation in respiratory infections: emerging strategies for therapeutic interventions - Globenko, Alexander A.; Kuzin, Gennady V.; Rydlovskaya, Anastasia V.; Isaeva, Elena I.; Vetrova, Elizaveta N.; Pritchina, Tat’yana N.; Baranova, Ancha; Nebolsin, Vladimir E. (Frontiers in Pharmacology, 2023)
Acute respiratory viral infections (ARVI) are the most common illnesses worldwide. In some instances, mild cases of ARVI progress to hyperinflammatory responses, which are damaging to pulmonary tissue and requiring intensive care. Here we summarize available information on preclinical and clinical effects of XC221GI (1-[2-(1-methyl imidazole-4-yl)-ethyl]perhydroazin-2,6-dione), an oral drug with a favorable safety profile that has been tested in animal models of influenza, respiratory syncytial virus, highly pathogenic coronavirus strains and other acute viral upper respiratory infections. XC221GI is capable of controlling IFN-gamma-driven inflammation as it is evident from the suppression of the production of soluble cytokines and chemokines, including IL-6, IL-8, CXCL10, CXCL9 and CXCL11 as well as a decrease in migration of neutrophils into the pulmonary tissue. An excellent safety profile of XC221GI, which is not metabolized by the liver, and its significant anti-inflammatory effects indicate utility of this compound in abating conversion of ambulatory cases of respiratory infections into the cases with aggravated presentation that require hospitalization. This drug is especially useful when rapid molecular assays determining viral species are impractical, or when direct antiviral drugs are not available. Moreover, XC221GI may be combined with direct antiviral drugs to enhance their therapeutic effects.